2015
DOI: 10.1111/nep.12433
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen in the treatment of calciphylaxis: A case series and literature review

Abstract: This retrospective analysis suggests a role for HBOT in the treatment of CUA with more than half of the treated patients benefiting and surviving for an average of more than 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 31 publications
0
36
0
2
Order By: Relevance
“…Systemic oxygenation strategies include the administration of erythropoietin to increase hematocrit levels, apparatus to effect continuous positive airway pressure, and whole-body chambers to produce an environment of 100% oxygen. 81,83,87,[110][111][112]377,378 Artery narrowing is already routinely counteracted by renal angioplasty with or without stenting and the administration of vasoconstriction inhibitors that target the renin-angiotensin-aldosterone system. 49,[379][380][381] The targeting of vasoconstriction pathways controlled through vasopressin, endothelin, and voltage dependent calcium channels are in their infancy, as is the use of vasodilators such as arginine and kallikrein.…”
Section: A New Hypoxia Paradigmmentioning
confidence: 99%
“…Systemic oxygenation strategies include the administration of erythropoietin to increase hematocrit levels, apparatus to effect continuous positive airway pressure, and whole-body chambers to produce an environment of 100% oxygen. 81,83,87,[110][111][112]377,378 Artery narrowing is already routinely counteracted by renal angioplasty with or without stenting and the administration of vasoconstriction inhibitors that target the renin-angiotensin-aldosterone system. 49,[379][380][381] The targeting of vasoconstriction pathways controlled through vasopressin, endothelin, and voltage dependent calcium channels are in their infancy, as is the use of vasodilators such as arginine and kallikrein.…”
Section: A New Hypoxia Paradigmmentioning
confidence: 99%
“…[14] Other treatment strategies include the use of non-calcium-based phosphate binders, bisphosphonates [13,15] and cinacalcet. [16] Intensified haemodialysis, hyperbaric oxygen [17] and sodium thiosulphate, the antioxidant cation chelator [18] used as a component of multimodal therapy, may have contributed to the favourable outcome in some series. [19] In this article we describe 19 patients with ESRD who presented with calciphylaxis, the majority of whom had received a renal transplant.…”
Section: Researchmentioning
confidence: 99%
“…Interventional studies are therefore needed to determine the role of a systemic decrease in fetuin-A followed by a systemic increase in the CPP levels regarding the pathogenesis of the patient's calciphylaxis. Recent clinical studies have shown the efficacy of STS and HOT in patients with calciphylaxis (17,22,23); STS has been shown to directly chelate calcium at the tissue level and to inhibit the oxidative stress that promotes vascular calcification. A retrospective review of 53 hemodialysis patients with calciphylaxis showed that the calciphylaxis diminished in 73% of patients after STS treatment (22).…”
Section: A B C Dmentioning
confidence: 99%
“…A retrospective review of 53 hemodialysis patients with calciphylaxis showed that the calciphylaxis diminished in 73% of patients after STS treatment (22). In addition, HOT is thought to facilitate wound healing through the reversal of tissue hypoxia (23). Although these newly introduced treatment modalities lack definitive evidence to support their use, the combination of STS and HOT should be considered in the treatment of calciphylaxis because the calciphylaxis-related mortality rate is still unacceptably high and because no interventions have proven to be totally effective.…”
Section: A B C Dmentioning
confidence: 99%